The role of leadership in financial and credit management for organizational stability in international firms - Waqeem Akram; Shehar Bano; Zeeshan Ali; Shumaila Akram (Priviet Social Sciences Journal, 2026)
International companies face complex and uncertain environments that require financial and credit control practices to ensure organizational stability, and leadership plays a pivotal role in determining these financial and credit management practices. This study employs a qualitative systematic literature review and thematic analysis to explore the relationship between leadership and financial governance, credit risk management, and organizational stability. This study synthesizes theoretical and empirical literature grounded in leadership theory, agency theory, and risk management theory to identify leadership dimensions that support organizational resilience. The results show six key themes: strategic financial vision, credit risk governance, adaptive leadership, ethical leadership, and embedding risk management in financial decision-making. The analysis implies that leadership is a governance tool that synchronizes financial systems, credit policies, and strategic goals in various regulatory and cultural contexts. This study is original in that it offers a qualitative analysis of leadership's role in international companies' financial governance and credit management practices, which provides a different view from previous studies. It also provides useful managerial insights for managers who want to build the financial strength and long-term sustainability of their organizations.